Why should obese youth be prioritized in COVID-19 vaccination programs? A nationwide retrospective study - Michelle G. Discacciati; Sirlei Siani; Ana Campa; Helder I Nakaya (Elsevier, 2022)
Summary: Background: The dominant effect of age on COVID-19 mortality obscures the impact of other risk factors. Although the elderly is at a greater risk of severe disease and death due to COVID-19, the interaction of obesity and age was not carefully assessed. This analysis is especially critical for prioritizing groups to receive COVID-19 vaccination. Methods: Starting with 1,120,767 unvaccinated individuals registered in a Brazilian surveillance system, we selected 313,898 hospitalized COVID-19 patients aged 20 to 89 who had a BMI ≥ 25 kg/m2 and cardiovascular diseases (CVD) or diabetes, as well as individuals with no risk factors associated with severe COVID-19. Patient data were stratified by age, obesity, BMI, and comorbidities, and subsequently, subjected to crude and adjusted odds ratio, hazard ratio, and Kaplan-Meier curves. Disease outcomes were invasive and non-invasive ventilatory support, intensive care unit (ICU) admission, and death. Findings: Obesity alone is a risk factor for in-hospital mortality and is more significant than cardiovascular disease and diabetes. Furthermore, obesity, cardiovascular disease, and diabetes increase the risk of severity and death by COVID-19 more significantly in young adults than in the elderly. When categorizing patients by obesity classes, the severity of obesity was found to be associated with a higher risk of admission to the ICU and death from COVID-19 than the non-obese young adults or elderly population. Interpretation: Our findings highlight the increased risk of severe COVID-19 on the Brazilian obese youth. As SARS-CoV-2 may become a recurrent seasonal infection, future vaccination campaigns against COVID-19 should prioritize obese young individuals. Fundings: This work was supported by the Brazilian National Council for Scientific and Technological Development (grant number 313662/2017-7 and 307356/2017-5; the São Paulo Research Foundation (grant numbers 2018/14933-2); and CAPES.